Positive electrode and lithium secondary battery manufactured using the same

By optimizing the ratio of fluorine-based binder to carbon and lithium transition metal phosphoric acid in the positive electrode active material layer of lithium secondary batteries, the challenges of high electrode resistance and low adhesion are addressed, resulting in improved energy density and resistance characteristics.

JP2025507778AActive Publication Date: 2025-03-21LG ENERGY SOLUTION LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024550863
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-11-03
Filing Date
2023-11-03
Publication Date
2025-03-21
Estimated Expiration
2043-11-03

AI Technical Summary

Technical Problem

Lithium iron phosphoric acid-based lithium secondary batteries face challenges with high electrode resistance due to the one-dimensional structure of the active material, which limits adhesion and energy density when attempting to reduce binder content.

Method used

A positive electrode active material layer is formulated with lithium transition metal phosphoric acid, a fluorine-based binder, and a conductive material, where the ratio of fluorine-based binder to carbon and lithium transition metal phosphoric acid is controlled between 0.7 to 1.7, and the binder content is minimized to enhance adhesion and reduce resistance.

Benefits of technology

The approach effectively reduces positive electrode resistance while maintaining excellent adhesion strength, allowing for increased energy density by optimizing the binder-to-active-material ratio and improving the conductivity and structural stability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507778000001
    Figure 2025507778000001
  • Figure 2025507778000002
    Figure 2025507778000002
  • Figure 2025507778000003
    Figure 2025507778000003
Patent Text Reader

Abstract

A positive electrode according to one embodiment of the present invention includes a positive electrode active material layer located on at least one surface of a positive electrode current collector, the positive electrode active material layer including a lithium transition metal phosphate, a fluorine-based binder, and a conductive material, the lithium transition metal phosphate including a carbon coating layer formed on a surface thereof, and a ratio (B / A) of a total weight B of the fluorine-based binder to a total weight A of the conductive material and carbon of the lithium transition metal phosphate in the positive electrode active material layer is 0.7 to 1.7.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2022-0145389, filed on November 3, 2022.

[0002] The present invention relates to a positive electrode and a lithium secondary battery having excellent adhesion and resistance characteristics even with a reduced binder content. [Background technology]

[0003] As technological development and demand for electric vehicles and energy storage systems (ESS) increases, the demand for batteries as energy sources is rapidly increasing, and various researches on batteries that can meet various requirements are being conducted accordingly. In particular, researches on lithium secondary batteries that have high energy density as a power source for such devices and have excellent life and cycle characteristics are being actively conducted.

[0004] Lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (LNCMO), lithium iron phosphate oxide (LFP), etc. are used as positive electrode active materials for lithium secondary batteries.

[0005] Lithium iron phosphate is low-cost because it contains iron, which is an abundant and low-cost material. In addition, lithium iron phosphate has low toxicity, so its use can reduce environmental pollution. Furthermore, because lithium iron phosphate has an olivine structure, the active material structure can be stably maintained at high temperatures compared to lithium transition metal oxides with a layered structure. This provides the advantage of excellent high-temperature stability and high-temperature life characteristics of the battery.

[0006] However, due to its structural characteristics, lithium ions in lithium iron phosphate can only move along one-dimensional paths, and so it has the disadvantages of a slower lithium ion diffusion rate and higher electrode resistance than lithium cobalt oxide (LCO) and lithium nickel cobalt manganese oxide (LNCMO), which have layered or spinel structures.

[0007] In order to improve such high electrode resistance, attempts have been made to coat the surface of the lithium iron phosphate with carbon or to increase the content of conductive material, but such attempts may lead to a decrease in the content of the positive electrode active material, causing a low energy density of the battery.

[0008] As another method for improving the positive electrode resistance, a method of reducing the binder content can be considered. However, there is a limit to how much the binder content can be reduced in order to manufacture a positive electrode having a certain level of adhesive strength.

[0009] Therefore, in the lithium iron phosphate-based positive electrode, there is a need to develop technology that improves the resistance characteristics without reducing the adhesive strength of the positive electrode. Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a positive electrode having a suitable level of adhesion performance while reducing the positive electrode resistance, and a lithium secondary battery having improved resistance characteristics. [Means for solving the problem]

[0011] According to one embodiment of the present invention, there is provided a positive electrode comprising a positive electrode active material layer located on at least one surface of a positive electrode current collector, the positive electrode active material layer comprising a lithium transition metal phosphate, a fluorine-based binder and a conductive material, the lithium transition metal phosphate comprising a carbon coating layer formed on a surface thereof, and a ratio (B / A) of a total weight B of the fluorine-based binder to a total weight A of the conductive material and carbon of the lithium transition metal phosphate in the positive electrode active material layer is 0.7 to 1.7.

[0012] In one embodiment of the present invention, the ratio (B / A) of the weight B of the fluorine-based binder to the total weight A of the conductive material and the carbon of the lithium transition metal phosphate in the positive electrode active material layer may be 0.72 to 1.3.

[0013] In one embodiment of the present invention, the fluorine-based binder may be contained in the positive electrode active material layer in an amount of 3 wt % or less.

[0014] In one embodiment of the present invention, the fluorine-based binder may be contained in the positive electrode active material layer in an amount of 1.6 to 2.7 wt %.

[0015] In one embodiment of the present invention, the positive electrode active material layer may have a porosity according to the following formula 1 in the range of 25 to 30%.

[0016] [Formula 1] Porosity (%) = {1 - (measured density of positive electrode active material layer / true density of positive electrode active material)} x 100

[0017] In one embodiment of the present invention, the positive electrode active material layer may have a porosity according to the above formula 1 in the range of 26 to 29%.

[0018] In one embodiment of the present invention, the fluorine-based binder may include a first fluorine-based binder having a weight average molecular weight (Mw) of 500,000 g / mol to 750,000 g / mol, and a second fluorine-based binder having a weight average molecular weight (Mw) of 800,000 g / mol or more.

[0019] In one embodiment of the present invention, the first fluorine-based binder may be a homopolymer of polyvinylidene fluoride (PVDF).

[0020] In one embodiment of the present invention, the second fluorine-based binder may be polyvinylidene fluoride (PVDF) containing polar functional groups.

[0021] In one embodiment of the present invention, the second fluorine-based binder may have a weight average molecular weight (Mw) of 900,000 g / mol to 2,000,000 g / mol.

[0022] In one embodiment of the present invention, the weight ratio of the first fluorine-based binder to the second fluorine-based binder may be 2:3 to 3:1.

[0023] In one embodiment of the present invention, the ratio (D / C) of the weight D of the lithium transition metal phosphate to the total weight C of the fluorine-based binder in the positive electrode active material layer may be 32-82.

[0024] In one embodiment of the present invention, the lithium transition metal phosphate may be a compound represented by the following Chemical Formula 1:

[0025] [Chemical formula 1] Li 1+a M1 1-x M2 x (PO y-b )D b

[0026] In the above Chemical Formula 1, M1 is one or more elements selected from Fe, Mn, Co, Ni, Cu, Zn and Mg; M2 is one or more elements selected from any one of Groups 2 to 15, excluding element M1; D is at least one selected from the group consisting of F, S and N; -0.5≦a≦+0.5, 0≦x≦0.5, 3.95≦y≦4.05, and 0≦b≦1.

[0027] In one embodiment of the present invention, in the above Chemical Formula 1, M1 is Fe, and M2 may be at least one selected from the group consisting of Al, Mg, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y.

[0028] In one embodiment of the present invention, the loading amount of the positive electrode active material layer is 450 to 650 mg / 25 cm 2 The range may be:

[0029] In one embodiment of the present invention, the conductive material may be carbon nanotubes.

[0030] In one embodiment of the present invention, the positive electrode active material layer may further include a hydrogenated nitrile-butadiene rubber.

[0031] According to another embodiment of the present invention, there is provided a lithium secondary battery including the positive electrode described above. Effect of the Invention

[0032] The positive electrode according to the present invention has an effect of reducing the positive electrode resistance while having excellent adhesive strength by controlling the value of B / A, which is the ratio of the total weight B of the fluorine-based binder to the total weight A of carbon that contributes to the conductive performance in the positive electrode active material layer, within an optimal range.

[0033] In addition, the positive electrode according to the present invention has an effect of improving the energy density since the weight ratio of the lithium transition metal phosphate can be increased even with a smaller binder content than the conventional positive electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] The advantages and features of the present invention, and the methods for achieving them, will become clear from the detailed description of the embodiments below in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms, and the present embodiments are provided solely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is only defined by the scope of the claims. The same reference numerals refer to the same elements throughout the specification.

[0035] Unless otherwise defined, all terms (including technical and scientific terms) used herein may be used as commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless otherwise clearly defined.

[0036] The terms used in this specification are for the purpose of describing the embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified in the phrase. The words "comprises" and / or "comprising" used in the specification do not exclude the presence or addition of one or more other components other than the components mentioned.

[0037] In this specification, when a part includes a certain component, this does not mean that it excludes other components, and it means that it may further include other components, unless specifically stated to the contrary.

[0038] In this specification, the phrase "A and / or B" means A or B, or A and B.

[0039] In this specification, "%" means % by weight unless expressly indicated otherwise.

[0040] In this specification, D 50D means the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 can be measured, for example, by using a laser diffraction method. The laser diffraction method generally enables measurement of particle sizes from the submicron range to several mm, and can provide results with high reproducibility and high resolution.

[0041] In this specification, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-miniII manufactured by BEL Japan.

[0042] In this specification, the total weight A of the carbon of the conductive material and the positive electrode active material is the total weight of the carbon material contributing to the conductive performance of the positive electrode, and means the weight obtained by subtracting the weight of the carbon contained in the fluorine-based binder from the total weight of the carbon contained in the positive electrode active material layer. Specifically, the total weight of the carbon contained in the positive electrode active material layer can be calculated from the total amount of CO2 generated by burning the positive electrode active material layer using a CS Analyzer after separating the positive electrode active material layer from the positive electrode current collector. The weight of the carbon contained in the fluorine-based binder can be calculated by measuring the fluorine content using ion chromatography after collecting the gas generated by burning the positive electrode active material layer in a combustion tube and diluting the collected absorption solution, and then calculating the measured fluorine content and the composition of the fluorine-based binder.

[0043] In the present specification, the term "weight average molecular weight (Mw)" refers to a value converted to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value converted from a value measured under the following conditions using GPC, and standard polystyrene from an Agilent system was used to create a calibration curve.

[0044] <Measurement conditions> Measuring instrument: Agilent GPC (Agulent 1200 series, USA) Column: PL Mixed B 2 pieces connected Column temperature: 40℃ Eluent: Tetrahydrofuran Flow rate: 1.0mL / min Concentration: ~1mg / mL (100μL injection)

[0045] The positive electrode adhesive strength in this specification can be measured by the following method. A positive electrode cut to a length of 150 mm and a width of 20 mm is prepared, and the positive electrode active material layer is placed facing a glass slide of a length of 75 mm and a width of 25 mm, and the positive electrode is attached to the glass slide in the longitudinal direction using double-sided tape. That is, the glass slide is attached to an area corresponding to half of the positive electrode in the longitudinal direction. Then, a roller is rolled 10 times so that the double-sided tape is evenly attached to prepare an evaluation sample. Next, the glass slide portion of the evaluation sample is fixed to the sample stage of a Universal Testing Machine (UTM) (LS5, AMETEK), and the half of the positive electrode to which the glass slide is not attached is connected to a load cell of the UTM equipment. The load cell is applied with a force of 90° at a speed of 100 mm / min and moved to 50 mm to measure the load applied to the load cell. At this time, the average load measured in a 20 mm to 40 mm section of the running section is calculated, and this is repeated five times in total, and the average value is evaluated as the positive electrode adhesive strength (gf / 20 mm) of each sample.

[0046] The present invention will be specifically described below.

[0047] <Positive electrode> A positive electrode according to one embodiment of the present invention includes a positive electrode active material layer located on at least one surface of a positive electrode current collector, the positive electrode active material layer including a lithium transition metal phosphate, a fluorine-based binder, and a conductive material, the lithium transition metal phosphate including a carbon coating layer formed on a surface thereof, and a ratio (B / A) of a total weight B of the fluorine-based binder to a total weight A of the conductive material and carbon of the lithium transition metal phosphate in the positive electrode active material layer may be in the range of 0.7 to 1.7.

[0048] The inventors of the present invention have conducted extensive research to improve the resistance characteristics of a positive electrode containing a lithium transition metal phosphate-based positive electrode active material without reducing adhesion. As a result, they have discovered that when the ratio (B / A) of the total weight B of the fluorine-based binder to the total weight A of the conductive material and carbon of the positive electrode active material that contribute to the conductive performance in the positive electrode active material layer is 0.7 to 1.7, even if the total content of the fluorine-based binder contained in the positive electrode active material layer is reduced, the positive electrode resistance is reduced while maintaining suitable adhesion performance, and have arrived at the present invention.

[0049] The positive electrode according to the embodiment of the present invention has a suitable level of adhesive performance even with a binder content lower than that of the conventional positive electrode by controlling the value of B / A, which is the ratio of the total weight B of the fluorine-based binder to the total weight A of the carbon that contributes to the conductive performance, within an acceptable range. In addition, the binder content in the positive electrode active material layer is reduced, improving the resistance characteristics, and the weight ratio of the positive electrode active material can be increased by the amount of binder that is reduced, so that the energy density per weight of the positive electrode can be increased. The value of B / A is a parameter that controls not only the electrical performance of the electrode such as conductivity, but also the physical performance of the electrode such as adhesive force, so that a positive electrode with good electrical / physical balance can be manufactured by appropriately controlling and limiting the value of B / A, which is an effect that cannot be achieved by a method of separately controlling electrical performance and physical performance.

[0050] The positive electrode according to the present invention will be specifically described.

[0051] A positive electrode according to an embodiment of the present invention may include a positive electrode active material layer. Specifically, the positive electrode according to the present invention may include a positive electrode current collector and the positive electrode active material layer located on at least one surface of the positive electrode current collector.

[0052] The positive electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, the current collector may be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like.

[0053] The positive electrode current collector may have a thickness of 3 μm to 500 μm, and may have fine irregularities on its surface to enhance adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0054] The positive electrode active material layer may include a positive electrode active material. Additionally, the positive electrode active material layer may further include a conductive material, a binder, and a dispersant, if necessary, in addition to the positive electrode active material.

[0055] Hereinafter, each component contained in the positive electrode active material layer will be specifically described.

[0056] (1) Positive electrode active material The present invention includes a lithium transition metal phosphate as a positive electrode active material. Since the lithium transition metal phosphate has an olivine structure, the active material structure is more stable at high temperatures than lithium transition metal oxides having a layered structure. As a result, when the lithium transition metal phosphate is used as a positive electrode active material, the high temperature stability and high temperature life characteristics of the positive electrode are significantly improved, thereby reducing the risk of fire in a lithium secondary battery including the positive electrode.

[0057] The lithium transition metal phosphate may be a compound represented by the following Formula 1:

[0058] [Chemical formula 1] Li1+a M1 1-x M2 x (PO y-b )D b

[0059] In the above Chemical Formula 1, M1 is one or more elements selected from Fe, Mn, Co, Ni, Cu, Zn and Mg; M2 is one or more elements selected from any one of Groups 2 to 15, excluding element M1; D is at least one selected from the group consisting of F, S and N; -0.5≦a≦+0.5, 0≦x≦0.5, 3.95≦y≦4.05, and 0≦b≦1.

[0060] According to a specific embodiment of the present invention, in the lithium transition metal phosphate, M1 is Fe, and M2 is at least one selected from the group consisting of Al, Mg, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y. Specifically, the lithium transition metal phosphate may be lithium iron phosphate (LiFePO4).

[0061] The lithium transition metal phosphate may be in the form of secondary particles formed by agglomeration of primary particles, or may have a monolithic structure consisting of primary particles.

[0062] In the present invention, the term "monolith structure" refers to a structure in which particles are not aggregated with each other in terms of morphology and exist in independent phases. A particle structure that is contrasted with this monolith structure is a structure in which small particles ("primary particles") are physically and / or chemically aggregated to form relatively large particles ("secondary particles").

[0063] When the lithium transition metal phosphate has a monolithic structure consisting of primary particles, the migration of the binder during the drying process of the positive electrode slurry can be mitigated, and thus the interfacial adhesion between the positive electrode current collector and the positive electrode active material layer can be improved.

[0064] Meanwhile, when the lithium transition metal phosphate is a secondary particle, the lithium transition metal phosphate may further include a hollow core part inside the secondary particle. By intentionally weakening the mechanical strength by forming a hollow inside the secondary particle, the secondary particle may be collapsed and turned into a primary particle during a rolling process, thereby reducing the springback phenomenon.

[0065] In one embodiment, the diameter of the hollow core portion may be 4 μm to 12 μm, preferably 5 μm to 11 μm. When the diameter of the hollow core portion satisfies the above range, the springback phenomenon does not occur excessively, the collapse rate of secondary particles is reduced, and the processability and productivity are not reduced. In the present invention, the measurement of the diameter of the hollow core portion is not particularly limited, and may be measured, for example, by scanning electron microscope (SEM).

[0066] The lithium transition metal phosphate may include a carbon coating layer on the surface. When a carbon coating layer is formed on the surface of the lithium transition metal phosphate, the electrical conductivity is improved and the resistance characteristics of the positive electrode may be improved.

[0067] The carbon coating layer may be formed using at least one raw material selected from the group consisting of glucose, sucrose, lactose, starch, oligosaccharides, polyoligosaccharides, fructose, cellulose, furfuryl alcohol polymers, ethylene and ethylene oxide block copolymers, vinyl resins, cellulose resins, phenol resins, pitch resins, and tar resins. Specifically, the carbon coating layer may be formed by mixing the raw material with the lithium transition metal phosphate and then heat treating the mixture.

[0068] Average particle size of lithium transition metal phosphate D50 The average particle diameter D of the positive electrode active material may be 0.8 μm to 20.0 μm, specifically 0.9 μm to 10.0 μm, and more specifically 0.9 μm to 3.0 μm. 50 When satisfies the above range, the mobility of lithium in the lithium transition metal phosphate is improved, and the charge / discharge characteristics of the battery can be improved.

[0069] The BET specific surface area of ​​lithium transition metal phosphate is 5m 2 / g~20m 2 / g, specifically 7m 2 / g~18m 2 / g, more specifically 9m 2 / g~16m 2 When this range is satisfied, aggregation of the lithium transition metal phosphate can be effectively suppressed even in a positive electrode slurry composition having a relatively low content of a dispersant.

[0070] The lithium transition metal phosphate may be contained in the positive electrode active material layer at 95% by weight to 99% by weight, specifically 95.5% by weight to 98.5% by weight, and more specifically 96% by weight to 98% by weight. When the content of the lithium transition metal phosphate satisfies the above range, the battery capacity of the positive electrode can be improved by ensuring a sufficient positive electrode energy density. The energy density of the cell including the positive electrode according to the present invention may be 300 Wh / L or more, specifically 320 to 400 Wh / L, and more specifically 330 to 400 Wh / L. Here, the above energy density is the energy density of a full cell.

[0071] (2) Binder The present invention contains a fluorine-based binder as the binder, and the fluorine-based binder imparts adhesive strength between the positive electrode active material and the conductive material, and adhesive strength between the current collector and the positive electrode active material layer.

[0072] The fluorine-based binder may be a PVDF-based polymer containing vinylidene fluoride (VDF) as a monomer. Specific examples of the PVDF-based polymer include PVDF single polymer, PVDF-HFP (Poly(vinylidene fluoride-co-hexafluoropropylene)), PVDF-CTFE (Poly(vinylidene fluoride-co-chlorotrifluoroethylene)), PVDF-TFE (Poly(vinylidene tetrafluoroethylene)), and PVDF-TrFE (Poly(vinylidene trifluoroethylene)).

[0073] In order to reduce the electrode resistance while maintaining the same level of positive electrode adhesive strength as other conventional positive electrodes, the content of the fluorine-based binder contained in the positive electrode active material layer is controlled in relation to the conductivity of the positive electrode active material layer. Specifically, the ratio (B / A) of the total weight B of the fluorine-based binder to the total weight A of the conductive material and the carbon of the positive electrode active material that contribute to the conductive performance in the positive electrode active material layer is controlled to satisfy 0.7 to 1.7.

[0074] In a preferred embodiment of the present invention, the B / A value may be 0.72 to 1.3, and more preferably 0.8 to 1.25. When the B / A value is within the above range, the positive electrode active material layer can have excellent resistance characteristics while having adhesion performance that is free from the risk of detachment.

[0075] In one embodiment of the present invention, the fluorine-based binder may include a first fluorine-based binder and a second fluorine-based binder having different numerical ranges of weight average molecular weight (Mw).

[0076] In one embodiment of the present invention, the first fluorine-based binder may have a weight average molecular weight (Mw) of 500,000 g / mol to 750,000 g / mol, preferably 550,000 g / mol to 730,000 g / mol, and more preferably 580,000 g / mol to 700,000 g / mol. The first fluorine-based binder imparts adhesive strength between the positive electrode active material and the conductive material, and adhesive strength between the current collector and the positive electrode active material layer.

[0077] In a preferred embodiment of the present invention, the first fluorine-based binder may be a homopolymer of polyvinylidene fluoride (PVDF). Since the homopolymer polyvinylidene fluoride (PVDF) contains a small number of polar functional groups such as -COOH, the functional groups of the binder can reduce the number of hydrogen bonds between hydrogen on the carbon coating layer coated on the surface of the lithium transition metal phosphate particles, thereby preventing gelation of the positive electrode slurry, improving the coating processability of the positive electrode slurry, and providing a uniform thickness and / or surface of the coated positive electrode active material layer, which is advantageous in that the output performance and life characteristics of a lithium secondary battery manufactured using the positive electrode are excellent.

[0078] The second fluorine-based binder may have a weight average molecular weight (Mw) of 800,000 g / mol or more, preferably 900,000 g / mol to 2,000,000 g / mol, more preferably 1,000,000 g / mol to 1,500,000 g / mol. The second fluorine-based binder exerts a synergistic effect with the first fluorine-based binder, and may reduce the total content of the fluorine-based binder contained in the positive electrode active material layer without inducing a decrease in adhesive strength. That is, if the total weight percent of the fluorine-based binder contained in the positive electrode active material layer is the same, a positive electrode containing both the first fluorine-based binder and the second fluorine-based binder has better adhesive performance than a positive electrode containing only the first fluorine-based binder. Therefore, when the first fluorine-based binder and the second fluorine-based binder are used in combination, even if the total weight percent of the fluorine-based binder contained in the positive electrode active material layer is reduced, the adhesive performance is not deteriorated and the reduced binder content can further improve the resistance characteristics.

[0079] In a preferred embodiment of the present invention, the second fluorine-based binder may be polyvinylidene fluoride (PVDF) containing a polar functional group. When the second fluorine-based binder contains a polar functional group, the crystallinity of the second fluorine-based binder is reduced, which can improve the flexibility of the positive electrode active material layer. Due to the improved flexibility of the positive electrode active material layer, the positive electrode active material layer does not detach from the positive electrode current collector even when an external stress is applied, and as a result, the adhesive strength of the positive electrode can be improved.

[0080] In a preferred embodiment of the present invention, the fluorine-based binder is contained in the positive electrode active material layer in an amount of 3 wt % or less, more preferably 1.6 to 2.7 wt %. In terms of the resistance characteristics of the positive electrode, the content of the fluorine-based binder is preferably in the above numerical range.

[0081] In a preferred embodiment of the present invention, the weight ratio of the first fluorine-based binder to the second fluorine-based binder may be 2:3 to 3:1, and preferably 1:1 to 2:1. If the content of the first fluorine-based binder is too high, it may be undesirable in terms of adhesion performance, and if the content of the second fluorine-based binder is too high, it may be undesirable because gelation of the positive electrode slurry may be induced.

[0082] In a preferred embodiment of the present invention, the ratio of the weight D of the lithium transition metal phosphate as the positive electrode active material to the total weight C of the first fluorine-based binder and the second fluorine-based binder may be 32 to 82, preferably 34 to 72, and more preferably 36 to 60. When the ratio of the weight D of the lithium transition metal phosphate as the positive electrode active material to the total weight C of the first fluorine-based binder and the second fluorine-based binder is within the above numerical range, both the capacity characteristics and adhesion performance of the positive electrode can be maintained at suitable levels.

[0083] (3) Conductive material The positive electrode active material layer of the present invention may further contain a conductive material.

[0084] The conductive material is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and may be, for example, graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. Specific examples of commercially available conductive materials include acetylene black series products of Chevron Chemical Company, Denka Black (Denka Singapore Private Limited), Gulf Oil Company (Gulf Oil Company products, etc.), Ketjenblack, EC series (Armak Company products), Vulcan XC-72 (Cabot Company products), and Super P (Timcal product). Preferably, the conductive material may be carbon nanotubes. When the conductive material is carbon nanotubes, the excellent conductive network of the carbon nanotubes can suppress the binder migration phenomenon in which the binder moves to the electrode surface when the electrode is dried, and can further improve the interfacial adhesion between the positive electrode current collector and the positive electrode active material layer.

[0085] The conductive material may be contained in the positive electrode active material layer at 0.3 wt% to 2.0 wt%, specifically 0.4 wt% to 1.5 wt%, more specifically 0.5 wt% to 1.3 wt%. When the content of the conductive material in the positive electrode active material layer satisfies the above range, the positive electrode conductive network is ensured, thereby improving the electrical conductivity of the positive electrode.

[0086] According to one embodiment of the present invention, the positive electrode active material layer may contain 96-98 wt% positive electrode active material, 0.8-1.3 wt% conductive material, and 1.2-3.0 wt% binder. When the composition in the positive electrode active material layer satisfies the above-mentioned range, the adhesive strength and conductivity of the electrode are ensured, and at the same time, the content of the active material is increased, so that the capacity and resistance performance of a lithium secondary battery including the positive electrode are excellent.

[0087] (4) Dispersants The positive electrode active material layer of the present invention may further contain a dispersant.

[0088] The dispersant prevents the lithium transition metal phosphate from being excessively aggregated in the positive electrode slurry composition, allowing the lithium transition metal phosphate to be effectively dispersed and present in the prepared positive electrode active material layer.

[0089] The dispersant may include a hydrogenated nitrile-based copolymer, and specifically, the dispersant may be a hydrogenated nitrile-based copolymer.

[0090] Specifically, the hydrogenated nitrile copolymer may be a copolymer containing an α,β-unsaturated nitrile-derived structural unit and a hydrogenated conjugated diene-derived structural unit, or a copolymer containing an α,β-unsaturated nitrile-derived structural unit, a conjugated diene-derived structural unit, and a hydrogenated conjugated diene-derived structural unit. As the α,β-unsaturated nitrile monomer, for example, acrylonitrile or methacrylonitrile may be used, and one or a mixture of two or more of these may be used. As the conjugated diene monomer, for example, a conjugated diene monomer having 4 to 6 carbon atoms such as 1,3-butadiene, isoprene, or 2,3-methylbutadiene may be used, and one or a mixture of two or more of these may be used.

[0091] More specifically, the hydrogenated nitrile copolymer may be hydrogenated nitrile butadiene rubber (H-NBR). At this time, the hydrogenated nitrile butadiene rubber may have a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol, preferably 15,000 g / mol to 90,000 g / mol, and more preferably 20,000 g / mol to 50,000. When the hydrogenated nitrile butadiene rubber satisfies the above numerical range, it has an excellent effect of suppressing the aggregation of the conductive material, and even if the conductive material is aggregated, it is aggregated in a spherical shape rather than a linear shape, so that the specific surface area of ​​the aggregated conductive material can be minimized compared to the case where the conductive material is aggregated in a linear shape. As a result, the surface area of ​​the positive electrode active material that is adjacent to the aggregated conductive material and cannot participate in the lithium insertion / extraction reaction is minimized, so that the discharge resistance of the lithium secondary battery can be reduced.

[0092] The dispersant may be included in an amount of 0.1 wt % to 2.0 wt %, specifically 0.2 wt % to 1.8 wt %, more specifically 0.3 wt % to 1.6 wt %, based on the total solid content of the positive electrode slurry composition. When the content of the dispersant satisfies the above range, aggregation of the positive electrode active material can be suppressed, and gelation of the positive electrode slurry composition can be prevented.

[0093] The positive electrode according to the present invention can be manufactured according to a conventional method for manufacturing a positive electrode. Specifically, the positive electrode can be manufactured by preparing a positive electrode slurry composition containing the above-mentioned positive electrode active material, conductive material, binder and / or dispersant, applying the positive electrode slurry composition onto a positive electrode current collector, and then drying and rolling the composition.

[0094] Alternatively, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0095] In one embodiment of the present invention, the loading amount of the positive electrode active material layer is 450 to 650 mg / 25 cm 2 , preferably 500 to 650 mg / 25 cm 2, and most preferably 600 to 650 mg / 25 cm 2 The loading amount in the above range is larger than the loading amount of a general positive electrode and is suitable as a high-loading positive electrode.

[0096] In one embodiment of the present invention, the porosity of the positive electrode active material layer after rolling may be in the range of 25 to 30%, preferably 26 to 29%. Here, the porosity may be calculated according to the following formula 1. The true density in formula 1 means the density of only the part completely filled with material, excluding the gaps between the positive electrode active material particles.

[0097] [Formula 1] Porosity (%) = {1 - (measured density of positive electrode active material layer / true density of positive electrode active material)} x 100

[0098] When the porosity of the positive electrode active material layer satisfies the above numerical range, it is preferable from the viewpoint of the adhesive performance and capacity of the positive electrode.

[0099] The positive electrode according to an embodiment of the present invention has excellent positive electrode adhesive strength and resistance characteristics, so that a high loading positive electrode can be manufactured. Since detachment of the positive electrode is prevented, the cell resistance of the secondary battery can be reduced, the capacity and output characteristics of the battery can be improved, and defects occurring during the manufacturing process can be reduced.

[0100] In the positive electrode of the present invention, the adhesive strength between the positive electrode current collector and the positive electrode active material layer measured by a 90° peel test may be 19 gf / 20 mm or more, specifically 20 gf / 20 mm or more, specifically 20 to 45 gf / 20 mm, specifically 20 to 40 gf / 20 mm. When the positive electrode has an adhesive strength of at least the above numerical value, it is preferable because the detachment of the positive electrode active material layer during the manufacturing process can be prevented.

[0101] The positive electrode of the present invention may have a direct current resistance (DCIR) of 1.91Ω or less, specifically 1.5 to 1.85Ω, more specifically 1.6 to 1.82Ω, relative to the voltage drop measured at a temperature of 25°C, a state of charge of SOC 30%, and a discharge pulse (pulse) of 0.5C for 10 seconds. The direct current resistance (DCIR) of 1.7Ω or less, specifically 1.4 to 1.69Ω, more specifically 1.45 to 1.68Ω, relative to the voltage drop measured at a temperature of 25°C, a state of charge of SOC 30%, and a discharge pulse (pulse) of 2C for 10 seconds. The method for measuring the direct current resistance is as described in Experimental Example 3 below.

[0102] <Lithium secondary battery> Next, the lithium secondary battery according to the present invention will be described.

[0103] A lithium secondary battery according to an embodiment of the present invention may include a positive electrode, a negative electrode, a separator interposed between the negative electrode, and an electrolyte.

[0104] The positive electrode in the lithium secondary battery is as described above. For example, the positive electrode includes a positive electrode active material layer located on at least one surface of a positive electrode current collector, the positive electrode active material layer includes a lithium transition metal phosphate, a fluorine-based binder, and a conductive material, the lithium transition metal phosphate includes a carbon coating layer formed on the surface, the ratio (B / A) of the total weight B of the fluorine-based binder to the total weight A of the conductive material and the carbon of the lithium transition metal phosphate in the positive electrode active material layer is 0.7 to 1.7, and preferably the fluorine-based binder may include a first fluorine-based binder having a weight average molecular weight (Mw) of 500,000 g / mol to 750,000 g / mol, and a second fluorine-based binder having a weight average molecular weight (Mw) of 800,000 g / mol or more.

[0105] Additionally, the positive electrode may further include a conductive material and a dispersant.

[0106] The negative electrode can be manufactured, for example, by preparing a composition for forming a negative electrode, which contains a negative electrode active material, a negative electrode binder, and a negative electrode conductive material, on a negative electrode current collector, and then coating the composition on the negative electrode current collector.

[0107] The negative electrode active material is not particularly limited, and can generally use a compound capable of reversible intercalation and deintercalation of lithium.Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, and highly crystalline carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; or a composite containing a metallic compound and a carbonaceous material. In addition, examples of low crystalline carbon include soft carbon and hard carbon, and examples of high crystalline carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. Among these, one type alone or a mixture of two or more types may be used, and a metallic lithium thin film may also be used as the negative electrode active material.

[0108] The negative electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The negative electrode conductive material may be generally contained in an amount of 1 to 30% by weight, specifically 1 to 20% by weight, and more specifically 1 to 10% by weight, based on the total weight of the negative electrode active material layer.

[0109] The negative electrode binder plays a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The negative electrode binder may be included in an amount of 1 to 30% by weight, specifically 1 to 20% by weight, more specifically 1 to 10% by weight, based on the total weight of the negative electrode active material layer.

[0110] Meanwhile, the negative electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, aluminum-cadmium alloy, etc. may be used.

[0111] In addition, the negative electrode current collector may typically have a thickness of 3 to 500 μm, and like the positive electrode current collector, the negative electrode current collector may have fine irregularities on its surface to enhance the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0112] Meanwhile, in the lithium secondary battery, the separator can be any one that is generally used as a separator in a lithium secondary battery, and is particularly preferred to have low resistance to ion migration of the electrolyte and excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof, can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. can also be used. In addition, the separator can be a porous thin film having a pore diameter of 0.01 μm to 10 μm and a thickness of 5 μm to 300 μm.

[0113] Meanwhile, in the lithium secondary battery, the electrolyte may include an organic solvent and a lithium salt that are commonly used in electrolytes, and is not particularly limited.

[0114] The organic solvent may be used without any particular limitation as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; or a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), or propylene carbonate (PC).

[0115] Among these, carbonate-based solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant, which can improve the charge / discharge performance of the battery, and low-viscosity linear carbonate-based compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) are more preferred.

[0116] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably contained in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.

[0117] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.

[0118] The lithium secondary battery of the present invention may be manufactured by forming an electrode assembly by disposing a separator between a positive electrode and a negative electrode, and then inserting the electrode assembly into a cylindrical or prismatic battery case and then injecting an electrolyte into the battery case. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and then inserted into a battery case and sealed.

[0119] When manufacturing the lithium secondary battery of the present invention, the electrode assembly may be dried to remove at least one organic solvent used in manufacturing the positive electrode, selected from the group consisting of N-methyl-2-pyrrolidone (NMP), acetone, ethanol, propylene carbonate, ethyl methyl carbonate, ethylene carbonate, and dimethyl carbonate. If an electrolyte having the same composition as the organic solvent used in manufacturing the positive electrode is used as the electrolyte, the process of drying the electrode assembly may be omitted.

[0120] Unlike the above-described lithium secondary batteries, the lithium secondary battery according to another embodiment of the present invention may be an all-solid-state battery.

[0121] The battery case may be one commonly used in the art, and the shape of the battery case is not limited depending on the application of the battery. For example, the battery case may be a cylindrical type using a can, a square type, a pouch type, a coin type, or the like.

[0122] The lithium secondary battery according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, energy storage systems (ESS), and electric vehicles such as hybrid electric vehicles (HEV), etc.

[0123] The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples alone.

[0124] <Example 1: Production of positive electrode>

[0125] (1) Preparation of positive electrode slurry Average particle size D of lithium transition metal phosphate 50LiFePO4, a primary particle with a single structure and a particle size of 1.0 μm, carbon nanotubes (CNT) as a conductive material, polyvinylidene fluoride (PVDF), a homopolymer with a weight average molecular weight (Mw) of 670,000 g / mol as a first fluorine-based binder, and polyvinylidene fluoride (PVDF), which contains a polar functional group and has a weight average molecular weight (Mw) of 1,000,000 g / mol as a second fluorine-based binder, were added to an N-methylpyrrolidone (NMP) solvent. The mixture was mixed at 2500 rpm for 90 minutes using homo-disperse to prepare a positive electrode slurry.

[0126] In the positive electrode slurry, the lithium transition metal phosphate, the conductive material, the first fluorine-based binder and the second fluorine-based binder were present in a weight ratio of 96.7:0.8:1.25:1.25, and the solids content of the positive electrode slurry was 62 wt %.

[0127] (2) Manufacturing of positive electrodes The above positive electrode slurry was applied at 600 mg / 25 cm on a 20 μm thick aluminum thin film. 2 After coating, the positive electrode slurry was dried with hot air at 130° C. for 5 minutes so that the solid content of the positive electrode slurry was 99.0 wt % or more. Then, the dried positive electrode slurry was rolled to prepare a positive electrode so that the porosity of the positive electrode active material layer was 27%.

[0128] At this time, the porosity was measured by a method according to the following formula 1.

[0129] [Formula 1] Porosity (%) = {1 - (measured density of positive electrode active material layer / true density of positive electrode active material)} x 100

[0130] <Examples 2 to 4: Production of Positive Electrodes>

[0131] A positive electrode was prepared in the same manner as in Example 1, except that the weight ratio of the lithium transition metal phosphate, the conductive material, the first fluorine-based binder, and the second fluorine-based binder in the positive electrode slurry was changed as shown in Table 1.

[0132] <Example 5: Production of positive electrode>

[0133] Average particle size D of lithium transition metal phosphate 50 LiFePO4, a primary particle with a single structure with a particle size of 1.0 μm, carbon nanotubes (CNT) as a conductive material, and polyvinylidene fluoride (PVDF), a homopolymer with a weight average molecular weight (Mw) of 670,000 g / mol as a binder, were added to an N-methylpyrrolidone (NMP) solvent. The mixture was mixed at 2500 rpm for 90 minutes using Homo-disperse to prepare a positive electrode slurry.

[0134] In the positive electrode slurry, the lithium transition metal phosphate, conductive material, and binder were present in a weight ratio of 96.2:0.8:3, and the solids content of the positive electrode slurry was 62 wt %.

[0135] <Example 6: Production of positive electrode>

[0136] A positive electrode was prepared in the same manner as in Example 5, except that the weight ratio of the lithium transition metal phosphate, the conductive material, and the binder in the positive electrode slurry was changed as shown in Table 1.

[0137] <Comparative Example 1: Production of Positive Electrode>

[0138] A positive electrode was prepared in the same manner as in Example 1, except that the weight ratio of the lithium transition metal phosphate, the conductive material, the first fluorine-based binder, and the second fluorine-based binder in the positive electrode slurry was changed as shown in Table 1.

[0139] <Comparative Example 2: Production of Positive Electrode>

[0140] Average particle size D of lithium transition metal phosphate 50LiFePO4, a primary particle with a single structure and a particle size of 1.0 μm, carbon nanotubes (CNT) as a conductive material, and polyvinylidene fluoride (PVDF), which has a weight average molecular weight (Mw) of 1,000,000 g / mol and contains polar functional groups as a binder, were placed in an N-methylpyrrolidone (NMP) solvent.

[0141] In the positive electrode slurry, the lithium transition metal phosphate, conductive material, and binder were present in a weight ratio of 96.2:0.8:3, and the solids content of the positive electrode slurry was 62 wt %.

[0142] However, the viscosity of the positive electrode slurry was too high, and the target loading amount (600 mg / 25 cm) was not achieved on the positive electrode current collector. 2 ) could not be coated with the positive electrode slurry, and a positive electrode could not be produced.

[0143] <Comparative Example 3>

[0144] A positive electrode was prepared in the same manner as in Example 1, except that the weight ratio of the lithium transition metal phosphate, the conductive material, the first fluorine-based binder, and the second fluorine-based binder in the positive electrode slurry was changed as shown in Table 1.

[0145] <Experimental Example 1: Calculation of the ratio (B / A) of the total weight B of the fluorine-based binder to the total weight A of the carbon contained in the conductive material and the lithium transition metal phosphate in the positive electrode active material layer>

[0146] For each of the positive electrodes produced in Examples 1 to 6 and Comparative Examples 1 to 3, the ratio (B / A) of the total weight B of the fluorine-based binder to the total weight A of the carbon in the positive electrode active material layer was calculated, and the results are shown in Table 1.

[0147] First, the total weight A of the conductive material and the carbon of the positive electrode active material was calculated by subtracting the weight of the carbon contained in the fluorine-based binder from the total weight of the carbon contained in the positive electrode active material layer.

[0148] The total weight of carbon contained in the positive electrode active material layer was calculated using a CS Analyzer after separating the positive electrode active material layer from the current collector. Specifically, the total weight of carbon contained in the positive electrode active material layer was calculated from the total amount of CO2 generated by burning the positive electrode active material layer using a CS Analyzer.

[0149] The weight of carbon contained in the fluorine-based binder can be derived by measuring the weight of fluorine contained in the positive electrode active material layer, converting the measured weight of fluorine to the total weight (B) of the fluorine-based binder contained in the positive electrode active material layer, and then calculating the weight of carbon contained in the fluorine-based binder using the weight % that carbon accounts for in the fluorine-based binder.

[0150] The weight of fluorine contained in the positive electrode active material layer was measured as follows: the positive electrode active material layer was separated from the current collector, and the separated positive electrode active material layer was burned to collect the generated gas in an absorbing solution, and the collected absorbing solution was diluted, and then the weight of fluorine contained in the positive electrode active material layer was measured using ion chromatography.

[0151] The total weight B of the fluorine-based binder was the total weight (B) of the fluorine-based binder contained in the positive electrode active material layer calculated in the process of deriving the weight of carbon contained in the fluorine-based binder.

[0152] The total weight B of the fluorine-based binder relative to the total weight A of the conductive material and the carbon of the positive electrode active material calculated in this manner is shown in Table 1.

[0153] <Experimental Example 2: Evaluation of adhesive strength of positive electrode>

[0154] The positive electrodes produced in Examples 1 to 6 and Comparative Examples 1 to 3 were each vacuum-dried at 130° C. for 2 hours, and then the adhesive strength between the positive electrode active material layer and the positive electrode current collector was measured. The results are shown in Table 1.

[0155] Specifically, the positive electrodes produced in Examples 1 to 6 and Comparative Examples 1 to 3 were cut to a length of 150 mm and a width of 20 mm, and the surface of the positive electrode was attached to a slide glass having a length of 75 mm and a width of 25 mm in the longitudinal direction using double-sided tape. That is, the slide glass was attached to an area corresponding to half of the longitudinal direction of the positive electrode. Then, a roller was rotated 10 times to uniformly attach the double-sided tape to produce an evaluation sample.

[0156] Next, the glass slide portion of the evaluation sample was fixed to the sample stage of a Universal Testing Machine (UTM) (product name: LS5, manufacturer: LLOYD), and the positive electrode half to which the glass slide was not attached was connected to the load cell of the UTM equipment. The load cell was subjected to a 90° force at a speed of 100 mm / min, and the load applied to the load cell was measured as it was moved up to 50 mm. The average load measured in the 20 mm to 40 mm section of the travel section was calculated, and this was repeated a total of five times, and the average value was evaluated as the positive electrode adhesive strength (gf / 20 mm) of each sample.

[0157] <Experimental Example 3: Resistance Evaluation>

[0158] <Secondary battery manufacturing> A negative electrode slurry was prepared by mixing and stirring artificial graphite as a negative electrode active material, styrene-butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and carbon nanotubes (CNT) as a conductive material in a weight ratio of 95:3:1:1 with water.

[0159] The negative electrode slurry was applied to the copper thin film at a ratio of 295 mg / 25 cm. 2 After coating so as to obtain the above-mentioned negative electrode slurry, the negative electrode slurry was dried so that the solid content of the negative electrode slurry became 99.0% by weight or more, and then rolled to produce a negative electrode.

[0160] A polyolefin separator was interposed between the positive and negative electrodes of each of Examples 1 to 6 and Comparative Examples 1 to 3, and then an electrolyte was injected to manufacture the secondary batteries of the Examples and Comparative Examples. The electrolyte was prepared by adding 2% by weight of vinylene carbonate (VC) to a non-aqueous electrolyte solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7, and dissolving LiPF6 at 1M.

[0161] The secondary batteries thus fabricated were each activated by charging at a constant current of 0.1 C, and then degassed.

[0162] <Initial resistance measurement> Each of the secondary batteries fabricated above was charged to SOC100% at 1C, then charged to 3.7V at 0.33C CC under constant current-constant voltage (CC-CV) charging conditions at 25°C, and then discharged to 2.5V at 0.33C CC conditions with a 0.05C current cut. After three cycles of the above charge and discharge, the battery was charged to SOC30% and a discharge pulse was applied at 0.5C for 10 seconds. The voltage drop was measured and calculated according to the following formula: DCIR, and the results are shown in Table 1. DCIR was also calculated for the voltage drop measured when a discharge pulse was applied at 2.0C for 10 seconds. The results are shown in Table 1.

[0163] DCIR = (V0-V1) / I (V0 = voltage before the pulse, V1 = voltage 10 seconds after the pulse, I = applied current)

[0164] <Resistance increase rate after high temperature storage> The secondary battery was stored in a high temperature environment of 60°C for two weeks. After that, it was charged to a state of charge (SOC) of 30% at a temperature condition of 25°C, and then a discharge pulse was applied at 0.5C for 10 seconds. The voltage drop measured while the battery was then applied was used to calculate the DCIR according to the above formula. The resistance increase rate (%) after high temperature storage calculated by substituting this into the following formula (1) is shown in Table 1.

[0165] Equation (1): Resistance increase rate (%) = {(resistance after high-temperature storage - initial resistance) / initial resistance} x 100

[0166] [Table 1]

[0167] The positive electrodes according to Examples 1 to 6 have excellent adhesive strength, but the B / A value is within the range of 0.7 to 1.7, so that they have excellent resistance characteristics compared to the electrodes according to the comparative examples. The positive electrode according to Comparative Example 1, in which the B / A value is outside the range of 0.7 to 1.7, has a low binder content and low adhesive strength. The positive electrode according to Comparative Example 1 has a large initial DCIR and a large high-temperature resistance increase rate compared to the positive electrodes of Examples 1 to 6, even though it has the smallest total binder content. This is interpreted as the adhesive strength between the positive electrode current collector and the positive electrode active material layer is too small, so that the interface resistance increases, and the resistance increase rate increases significantly due to electrode detachment under high-temperature storage conditions. The positive electrode according to Comparative Example 3 has the best adhesive strength, but the B / A value exceeds 1.7, so that it has poor resistance characteristics.

[0168] It was also shown that the positive electrodes of Examples 1 and 2, in which the value of B / A was within the range of 0.72 to 1.3, had smaller initial DCIR and smaller high-temperature resistance increase rates than the positive electrodes of Examples 3 to 5. Therefore, it is found that in order to improve the resistance characteristics of the positive electrode, it is preferable that the value of B / A is within the range of 0.72 to 1.3.

[0169] <Example 7: Production of positive electrode>

[0170] A positive electrode was manufactured by preparing a positive electrode slurry having the same composition as that of Example 1, and a positive electrode was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was changed to 26% during rolling.

[0171] <Example 8: Production of positive electrode>

[0172] A positive electrode was manufactured by preparing a positive electrode slurry having the same composition as that of Example 1, and the positive electrode was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was changed to 28% during rolling.

[0173] <Example 9: Production of positive electrode>

[0174] A positive electrode was manufactured by preparing a positive electrode slurry having the same composition as that of Example 1, and by the same method as that of Example 1, except that the porosity of the positive electrode active material layer was changed to 30% during rolling.

[0175] <Comparative Example 4: Production of Positive Electrode>

[0176] A positive electrode was manufactured by preparing a positive electrode slurry having the same composition as that of Example 1, and the positive electrode was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was changed to 24% during rolling.

[0177] <Comparative Example 5: Production of Positive Electrode>

[0178] A positive electrode was manufactured by preparing a positive electrode slurry having the same composition as that of Example 1, and by the same method as that of Example 1, except that the porosity of the positive electrode active material layer was changed to 32% during rolling.

[0179] <Experimental Example 4: Adhesion Strength Evaluation>

[0180] The adhesive strength of each of the positive electrodes of Examples 7 to 9 and Comparative Examples 4 and 5 was measured in the same manner as in Experimental Example 2, and the results are shown in Table 2.

[0181] <Experimental Example 5: Capacity Evaluation>

[0182] <Secondary battery manufacturing> A lithium metal counter electrode was prepared as the negative electrode.

[0183] A polyolefin separator was interposed between the positive and negative electrodes of each of Examples 7 to 9 and Comparative Examples 4 to 5, and then an electrolyte was injected to manufacture the secondary batteries of the Examples and Comparative Examples. The electrolyte was prepared by adding 0.5% by weight of vinylene carbonate (VC) to a non-aqueous electrolyte solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 2:8, and dissolving LiPF6 at 1M.

[0184] Each of the fabricated secondary batteries was activated by charging at a constant current of 0.1 C and then degassed. Then, each battery was initially charged and discharged under the following conditions to measure the capacity, and the results are shown in Table 2.

[0185] Charging: 0.1C, CC / CV, 3.7V, 0.05C cut-off

[0186] Discharge: 0.1C, CC, 2.5V, cut-off

[0187] [Table 2]

[0188] Referring to Table 2, the positive electrode of Comparative Example 4, which has a porosity of less than 25%, was shown to have the best capacity characteristics, but had an adhesive strength of less than 20 gf / 20 mm, and was evaluated to have a risk of the positive electrode active material layer coming off. The positive electrode of Comparative Example 5, which has a porosity of more than 30%, was shown to have the best adhesive strength, but had a capacity of less than 157 mAh / g, and was evaluated to be unsuitable as a finished product. Therefore, the porosity of the positive electrode active material layer in the positive electrode according to the present invention is preferably in the range of 25 to 30%.

Claims

1. A positive electrode active material layer is disposed on at least one surface of a positive electrode current collector, the positive electrode active material layer includes a lithium transition metal phosphate, a fluorine-based binder, and a conductive material; The lithium transition metal phosphate includes a carbon coating layer formed on a surface thereof, A ratio (B / A) of a total weight B of the fluorine-based binder to a total weight A of the carbon of the conductive material and the lithium transition metal phosphate in the positive electrode active material layer is 0.7 to 1.

7.

2. 2. The positive electrode according to claim 1, wherein a ratio (B / A) of a weight B of the fluorine-based binder to a total weight A of the conductive material and the carbon of the lithium transition metal phosphate in the positive electrode active material layer is 0.72 to 1.

3.

3. The positive electrode according to claim 1 , wherein the fluorine-based binder is contained in the positive electrode active material layer in an amount of 3% by weight or less.

4. The positive electrode according to claim 1 , wherein the fluorine-based binder is contained in the positive electrode active material layer in an amount of 1.6 to 2.7% by weight.

5. The positive electrode according to claim 1, wherein the positive electrode active material layer has a porosity according to the following formula 1 in the range of 25 to 30%: [Formula 1] Porosity (%)={1−(measured density of positive electrode active material layer / true density of positive electrode active material)}×100.

6. The positive electrode according to claim 5 , wherein the positive electrode active material layer has a porosity according to formula 1 in the range of 26 to 29%.

7. 2. The positive electrode according to claim 1, wherein the fluorine-based binder comprises a first fluorine-based binder having a weight average molecular weight (Mw) of 500,000 g / mol to 750,000 g / mol, and a second fluorine-based binder having a weight average molecular weight (Mw) of 800,000 g / mol or more.

8. 8. The positive electrode of claim 7, wherein the first fluorine-based binder is a homopolymer of polyvinylidene fluoride (PVDF).

9. 8. The positive electrode of claim 7, wherein the second fluorine-based binder is polyvinylidene fluoride (PVDF) containing polar functional groups.

10. The positive electrode according to claim 7, wherein the second fluorine-based binder has a weight average molecular weight (Mw) of 900,000 g / mol to 2,000,000 g / mol.

11. The positive electrode according to claim 7, wherein the weight ratio of the first fluorine-based binder to the second fluorine-based binder is 2:3 to 3:

1.

12. 2. The positive electrode according to claim 1, wherein a ratio (D / C) of a weight D of the lithium transition metal phosphate to a total weight C of the fluorine-based binder in the positive electrode active material layer is 32 to 82.

13. The positive electrode according to claim 1 , wherein the lithium transition metal phosphate is represented by the following chemical formula 1: [Chemical formula 1] <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 1+a <h2 style=";text-align:left;direction:ltr"> 11<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> 12<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> ((PO<h2 style=";text-align:left;direction:ltr"> y-b <h2 style=";text-align:left;direction:ltr"> )D<h2 style=";text-align:left;direction:ltr"> b In the above Chemical Formula 1, M1 is one or more elements selected from Fe, Mn, Co, Ni, Cu, Zn, and Mg; M2 is one or more elements selected from any one of Groups 2 to 15, excluding element M1; D is at least one selected from the group consisting of F, S and N; -0.5≦a≦+0.5, 0≦x≦0.5, 3.95≦y≦4.05, and 0≦b≦1.

14. 14. The positive electrode of claim 13, wherein in Formula 1, M1 is Fe, and M2 is at least one selected from the group consisting of Al, Mg, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y.

15. The loading amount of the positive electrode active material layer is 450 to 650 mg / 25 cm 2 The positive electrode of claim 1 , wherein the ionic liquid is in the range of

16. The positive electrode of claim 1 , wherein the conductive material is a carbon nanotube.

17. 10. The positive electrode of claim 1, wherein the positive electrode active material layer further comprises hydrogenated nitrile butadiene rubber.

18. A lithium secondary battery comprising the positive electrode according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • High-temperature cyclic lithium iron phosphate power battery and manufacturing method thereof

    CN107768727A

  • Positive electrode and lithium battery including positive electrode

    JP2020035746A

  • Encapsulated cathode active material particles, lithium secondary battery containing same, and method of manufacture

    JP2020517055A

  • Positive-electrode materials: methods for their preparation and use in lithium secondary batteries

    KR1020140082988A

  • Composite binder composition for secondary battery, cathode and lithium battery containing the binder

    KR1020150033439A